2019
DOI: 10.1177/1040638719831413
|View full text |Cite
|
Sign up to set email alerts
|

Acute lead arsenate poisoning in beef cattle in Uruguay

Abstract: We describe and illustrate lesions in an outbreak of lead arsenate poisoning in beef cattle that ingested pesticide residues stored in an abandoned building of a former orange orchard. Of 70 exposed cattle, 14 had diarrhea, paresis, ataxia, recumbency, and/or seizures. Ten of the affected animals died after a clinical course of 12-18 h. Pathologic findings in 3 steers included extensive necrohemorrhagic, ulcerative rumenitis, omasitis, and abomasitis; lymphocytolysis in lymphoid organs; and nephrosis. Hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Other conditions that may produce similar mucosal lesions in the alimentary tract, and that have been described in Argentina and Uruguay, include intoxication by Ricinus communis , 10 lead arsenate, 14 and Baccharis corifidolia . 15 No exposure to any of these toxicants was observed in the animals in our outbreaks.…”
Section: Discussionmentioning
confidence: 69%
“…Other conditions that may produce similar mucosal lesions in the alimentary tract, and that have been described in Argentina and Uruguay, include intoxication by Ricinus communis , 10 lead arsenate, 14 and Baccharis corifidolia . 15 No exposure to any of these toxicants was observed in the animals in our outbreaks.…”
Section: Discussionmentioning
confidence: 69%
“…Toxic diseases that are characterized by similar lesions in the forestomachs include intoxications with the plant Baccharis coridifolia , 25 to which the cattle in our study were not exposed, trichothecenes, 20 and lead arsenate. 24 For this reason, we tested the beetles for the trichothecene T-2 toxin and for heavy metals (including lead and arsenic), which were not detected. In addition, in these diseases there are usually concurrent lesions such as necrosis of lymphoid organs, liver, and renal tubules that were not seen in any of the calves in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is further obscured by the fact that the clinical signs and lesions described in the affected animals are not exclusive of A. atromaculatus-associated disease and can be present in other conditions, including infectious and toxic diseases. 24,25,31 Therefore, the aims of this study were to assess the clinical and pathological effects of single oral administration of different doses of A. atromaculatus in cattle and search for putative toxic compounds in this insect species. This information is of value to clinicians, pathologists, and researchers working in the fields of toxicology, entomology, and animal nutrition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of Pb is quite significant, since recently Schild et al reported an outbreak of Pb poisoning in cattle in Uruguay due to PbHAsO 4 exposure, finding levels up to 9.4 mg kg −1 in the animal livers [28]. This compound is an environmentally hazardous insecticide, that has been banned from the market in many countries given its persistence and potential risk to public health.…”
Section: Application To Beef Samplesmentioning
confidence: 99%